Representative learning design in springboard diving: Is dry-land training representative of a pool dive? - Barris, S.; Davids, K.; Farrow, D. (European Journal of Sport Science, 2013)
Two distinctly separate training facilities (dry-land and aquatic) are routinely used in springboard diving and pose an interesting problem for learning, given the inherent differences in landing (head first vs. feet first) imposed by the different task constraints. Although divers may practise the same preparation phase, take-off and initial aerial rotation in both environments, there is no evidence to suggest that the tasks completed in the dry-land training environment are representative of those performed in the aquatic competition environment. The aim of this study was to compare the kinematics of the preparation phase of reverse dives routinely practised in each environment. Despite their high skill level, it was predicted that individual analyses of elite springboard divers would reveal differences in the joint coordination and board-work between take-offs. The two-dimensional kinematic characteristics were recorded during normal training sessions and used for intra-individual analysis. Kinematic characteristics of the preparatory take-off phase revealed differences in board-work (step lengths, jump height, board depression angles) for all participants at key events. However, the presence of scaled global topological characteristics suggested that all participants adopted similar joint coordination patterns in both environments. These findings suggest that the task constraints of wet and dry training environments are not similar, and highlight the need for coaches to consider representative learning designs in high performance diving programmes.